La place de l’ethnicité dans les conflits miniers socio-environnementaux dans les Andes du Pérou : XXème-XXIème siècles - Carmen Salazar-Soler (IdeAs)
This article concentrates on the place occupied by ethnicity in the discourses and practices of different actors of socio-environmental mining conflicts currently taking place in the Peruvian Andes. By analyzing discourses and practices put forward by the State, mining companies and various organizations opposed to mining activity, we introduce the issue of an emerging indigenous mining discourse. We focus on the representativity of this discourse amongst the local population and examine its national and international conditions of possibility. We show how some local populations ask to be recognized as “indigenous people (or communities)” and/or “native people”, in order to shield their territories from the impacts of mining activity with the Peruvian Law of Prior Consultation and the ILO Convention 169. We show how this self-identification as “indigenous peoples” or “native peoples” reflects a demand for effective citizenship recognition and increased participation to national politics on the side of marginalized sectors of Peruvian society.The article is divided in two parts. The first deals with the analysis of the place occupied by ethnicity in the discourse and practice of the Confederacion Nacional de Comunidades Afectadas por la Minera (Conacami). The second focuses on the stakes of implementing the Law of Prior Consultation for indigenous or native people in Andean Peru, and the place of ethnicity in these dynamics.